Comparison of Renal Anastomosing Hemangiomas in End-Stage and Non–End-Stage Kidneys: A Meta-Analysis With a Report of 2 Cases. (September 2017) - Berker, Neslihan Kayisoglu; Bayram, Aysel; Tas, Serap; Bakir, Baris; Caliskan, Yasar; Ozcan, Faruk; Kilicaslan, Isin; Ozluk, Yasemin
Background . Renal anastomosing hemangioma (RAH) is a very rare distinct entity composed of anastomosing sinusoidal (spleen-like) capillary-sized vessels lined by flat or hobnail endothelial cells. Most of the published cases of RAH occurred in the setting of end-stage renal disease (ESRD). Methods . We present 2 cases of RAH in ESRD along with a literature review. We compared clinicopathologic features of RAHs in end-stage and non–end-stage kidneys. A meta-analysis was conducted with PubMed and a manual search through references of relevant publications. Individual patient data gathered from the literature were used in the analysis. Results . Our systematic review revealed 49 RAHs, including our 2 cases. Thirty-two (65.3%) cases were in ESRD, only 17 (34.7%) were in patients with non-ESRD. RAHs in ESRD were in younger patients, smaller in size, multifocal, and seen more with renal epithelial neoplasms when compared with RAHs in non-ESRD ( P < .05). Extramedullary hematopoiesis was seen mostly in RAHs in ESRD kidneys (85% vs 41.7%) ( P = .018). Follow-up data were available for 25 cases with a mean follow-up of 24.58 ± 38.54 months. Recurrence, metastasis, or death have never been described related to RAH in any patients. Conclusions . In conclusion, RAHs are rare and mostly arise in kidneys with end-stage damage. RAHs in ESRD and non-ESRD differ in terms of clinicopathologic features.